Climate change and freshwater ecology: Hydrological and ecological methods of comparable complexity are needed to predict risk. (18th November 2020) - John, Andrew; Horne, Avril; Nathan, Rory; Stewardson, Michael; Webb, J. Angus; Wang, Jun; Poff, N. LeRoy
Abstract: Many freshwater ecosystems are in decline because of anthropogenic disturbance including climate change, yet our understanding of ecological vulnerability to future conditions including climatic variation is limited. Understanding climate risks to freshwater ecosystems requires combining hydrological and ecological knowledge. While there have been significant advances in ecohydrological approaches when applied within the large array of methods available for undertaking impact assessments, the ecological and hydrological elements are often not well‐integrated. This results in a mismatch in their ability to accommodate the inherent uncertainty in both impacts and responses. We examine published literature that assesses climate change impacts on freshwater ecosystems using both hydrological and ecological models to better understand method choices. We identify four fundamentally distinct modeling approaches used to assess climate change risk. We discuss which approaches are less useful for predicting ecological impacts under climate change, and highlight approaches of comparable complexity that can maximize the utility of dynamic, process‐based modeling while capturing the effects of climate uncertainty and variability. Using an illustrative case study of riparian vegetation health under climate change, we show how the four alternate modeling approaches feature different degrees of information in their outcomes and inferences about future risk. Most current studies that examine climate change risks to freshwater ecosystems use simplified methods or inadequately combine key elements. However, unless the interactions between changing hydrologic variability and ecological responses are explicitly captured in scale‐sensitive modeling methods, the risks of climate change to freshwater ecosystems will likely be substantially misrepresented, with negative consequences for effective management responses. Capturing these interactions requires combining ecological and hydrological methods of comparable complexity. This article is categorized under: Climate, Ecology, and Conservation > Modeling Species and Community Interactions Abstract : Combinations of alternate modeling methods lead to different kinds of outcomes when assessing climate change risk. Stochastic dynamic approaches which can project sequential ecological outcomes and accommodate climate variability are underrepresented in the literature.